Impact of Parent’s Communication on Adolescent Social Anxiety - Djudju Sriwenda; Elih Sudiapermana; Joni Rahmat Pramudia; Asep Saepudin; Juli Dwi Prasetyono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: Knowing the impact of parent’s communication and adolescent social anxiety. Method: The Research type is quantitative, using survey techniques with a teenage population. The sample size was 2135 junior high school students spread across 24 Cities and Districts in West Java. Data was collected for 1 month (October 1-31, 2024). Respondents filled out a Google form containing instruments about parental communication patterns (attitudes towards children's opinions, accepting criticism, involving children in decision-making, enforcing rules, etc) and social anxiety (fear of negative evaluation. social avoidance). Data analysis using Chi-Square and Pearson. Results: Most respondents were 14 years old and lived with their parents; their mother's education was junior high school, while their father's was high school. The position of the children was the first and last child. More than 10% of parents have authoritarian communication with adolescents, although most have democratic communication. There is a significant relationship between the age of respondents and the level of anxiety indicated by the results of the Pearson test with a P value of 0.032. In contrast, parental communication and adolescent social anxiety have a statistically significant relationship, indicated by a p-value of 0.01 using the chi-square test. Novelty: Social anxiety is rarely symptomatic, so parents should be able to recognize the condition early and improve communication patterns immediately